Persian Poets of Sind - Sadarangani, H. I. (Karachi Sindhi Adabi Board, 1956)
"Originally prepeared as a thesis for the degree of Doctor of Philosophy ... University of Bombay in 1946."
Include Bibliography and Index
Keywords: Persian poetry -- Pakistan--Sindh